Metabolomic profiling of Thyone aurea highlights the impact of solvent storage - Cassandra Upton; Gerhard Prinsloo; Paul Steenkamp; Moses Okpeku (Computational and Structural Biotechnology Journal)
Sea cucumbers, marine invertebrates increasingly recognised for their valuable biomolecules, are in growing demand due to the rising preference for marine products as safer, less toxic, and environmentally friendly alternatives to synthetic or terrestrial counterparts. Metabolomics analysis provides a comprehensive approach for investigating the metabolic dynamics of marine organisms, enabling the discovery of their nutritional and biochemical potential. This study aimed to perform an untargeted metabolomics analysis of Thyone aurea body tissue and crude storage-ethanol extracts using 1H NMR. Additionally, full-scan UPLC-QTOF-MS was used to confirm the NMR-metabolomics annotation and to provide more information on the chemical profile of T. aurea. Both the analytical techniques were used to assess the extent of metabolite leaching during solvent storage and its methodological implications for compound profiling. The analysis revealed distinct metabolite patterns between the tissue and extract, particularly for amino acids, triterpene glycosides, aliphatic organosulphates, and carboxylic acids. Overall, both the body tissue and storing-ethanol extracts demonstrated high metabolite potential and variability, emphasising the role of solvent storage in influencing metabolic profiles. These findings suggest that the chemical composition of sea cucumber samples can be significantly impacted by storage conditions, which must be carefully considered during metabolite profiling. Further research is warranted to elucidate the metabolic pathways of T. aurea and to expand our understanding of sea cucumbers more broadly. This study contributes to the growing field of marine metabolomics and establishes a foundation for future research on a wider range of lesser-studied, potentially endemic sea cucumber species.